How is public housing policy implemented in China?: A tentative analysis of the local implementation of four major programs - Fan, Yongmao; Yang, Hongshan (American Review of Public Administration)
One challenge that policy implementation studies face is how to build a structural framework using different variables. This article constructs a path-incentive model of implementation as an analytical framework with which to examine the relationship between central and local government. It consists of two key variables: policy path and incentive. The model embraces four types of implementation: administrative implementation, experimental implementation, flexible implementation, and symbolic implementation. Based on a case study of China$1 (Bs major public housing policies from 1998 to 2013, the article finds that even if policy goals and the implementation path are sometimes unclear, a strong top-down incentive mechanism will encourage local governments to actively engage in policy experiments. This local explorative approach can enhance an understanding of the policy environment and avoid apportioning blame to the central government for defective policy making. In China, policy implementation not only turns policy goals into real outcomes but also is a means of improving policy paths and incentive mechanisms. - Reproduced.s